Apport phenomena of medium Herbert Baumann (1911-1998): Report on personal experiences. - von Ludwiger, Illobrand; Nahm, Michael (Journal of Scientific Exploration, 2016)
Among the many phenomena reported from physical mediumship, apport phenomena – i. e. the inexplicable appearance of solid objects – rank among the most curious occurrences. In the present paper, we describe a selection of seeming apport phenomena that were observed around a German medium, Herbert Baumann (1911-1998), who seemed particularly able to produce apports,. Baumann was a close friend of the first author, who thus had the opportunity to receive more than one hundred examples of what he considers to be genuine apports, both during séances and in everyday private life. We then introduce the quantum theory of theoretical physicist Burkhard Heim (1925-2001) as an example of a physical theory that apparently can account for the occurrence of so-called psi-phenomena including apports.